The dilemmas of experimental CLIL in Catalonia. Issue 4 (21st April 2022) - Codó, Eva
ABSTRACT: In the early twenty-first century Content and Language Integrated Learning (CLIL) emerged as a distinctively European pedagogy for raising additional language competence. Although CLIL scholarship has been abundant and has taken many different directions, there is a dearth of ethnographic research to shed light on the situated ambivalences of CLIL policymaking. This paper aims to fill the existing gap by analysing in detail the complex interlocking dilemmas faced by all stakeholders (including policy makers and parents) at a Catalan state secondary school (Spain) and the ways in which they were navigated. Through a focused analysis of actors' discourse, triangulated with long-term classroom observations and a variety of other ethnographic data, the study argues that, despite the school's praiseworthy efforts at capitalising its students through English, CLIL did not achieve its full potential. This is attributed to the absence of explicitly-set and graded linguistic goals. Such absence is said to be shaped by the intersection of the experimental nature of the policy and long-standing linguistic ideologies in Catalan education. The article warns about the consequences of such indeterminacy for the democratising agenda of CLIL.